Klaster paprykowy w podregionie radomskim - próba identyfikacji - Gieżyńska, Halina (Bell Pepper Cluster in Radom's Subregion - an Attempt at Identification, 2007)
National agricultural census of 2002 has shown that in Poland the production of bell peppers in greenhouses is located mostly in Mazowieckie voivodship, and 70% of the entire production takes place in Przysuski, Białobrzeski and Radomski districts. This paper is an attempt to find out whether the territorial grouping of bell peppers producers in Radom's subregion can be considered a cluster, in view of M.E. Porter's cluster theory. Further analysis presents that such a grouping of producers in this subregion shows only partially the characteristics of a cluster and develops its competition practices basing almost only on factors connected with production conditions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 191-200